2021
DOI: 10.1007/s00402-021-04048-y
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and techniques of a new robotically assisted technique for total knee arthroplasty: the ROSA knee system

Abstract: IntroductionThe ROSA (Robotic Surgical Assistant) Knee system (Zimmer Biomet, Warsaw, IN) for total knee arthroplasty (TKA) can be considered as collaborative robotics, where the surgeon remains in charge of the procedure and collaborates with a smart robotic tool, to perform the surgery with a high accuracy and reproducibility. The aim was to describe: (1) its concept and surgical technique; (2) its advantages and potential limits; (3) the early experience with this system. Materials and methods The goal duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 34 publications
(41 reference statements)
0
40
0
1
Order By: Relevance
“…The robot-assisted system is a new technology which uses computed tomography (CT) data of patients’ lower limb to make a preoperative plan and three -dimensional planning to orientate and size and uses the robotic arm to cut the bone and place for components [ 23 , 24 ]. Several robotic-assisted TKA systems, including CASPAR, Tsolution, ROSA, ROBODOC and Mako, have been implemented into clinical application [ [25] , [26] , [27] , [28] ]. Previous studies showed that robotic-assisted TKA can offer more accurate bone cuts, precise placement of implants and provide balanced extension and flexion gaps [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The robot-assisted system is a new technology which uses computed tomography (CT) data of patients’ lower limb to make a preoperative plan and three -dimensional planning to orientate and size and uses the robotic arm to cut the bone and place for components [ 23 , 24 ]. Several robotic-assisted TKA systems, including CASPAR, Tsolution, ROSA, ROBODOC and Mako, have been implemented into clinical application [ [25] , [26] , [27] , [28] ]. Previous studies showed that robotic-assisted TKA can offer more accurate bone cuts, precise placement of implants and provide balanced extension and flexion gaps [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, there was no difference in operative times in ROSA TKA compared to those with a conventional jig-based TKA. In theory, RA TKA surgery should allow a more streamlined surgical approach by decreasing the need for alignment guides and cutting blocks and reducing the need for implant trialling [ 2 , 21 , 27 ]. Other studies with different RA TKA systems have found no difference between RA TKA and jig-based TKA after an initial learning phase [ 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ROSA® (Robotic Surgical Assistant) Knee system (Zimmer Biomet, Warsaw, Indiana, USA) for TKA was recently introduced. ROSA can be considered collaborative robotics, where the surgeon remains in charge of the procedure but collaborates with a smart robotic tool to perform the surgery with high accuracy and reproducibility [ 2 , 21 , 22 ]. The advantages of ROSA compared with other RA TKA include: requiring only radiographs for pre-operative planning, a collaborative robotic system where the robot completes the surgeon skills, and predictive robotics with machine learning incorporated into the system [ 2 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of autonomous surgical robots, which independently perform surgical procedures on humans by means of AI-controlled systems, remains a vision at the present time ( 17 , 18 ). Some surgical fields, such as orthopedic surgery, have shown promising advances in the use of robotic devices for specific tasks: Active robotic devices can help perform more precise bone cuts for total knee arhtroplasty using preoperative CT imagery with very good results ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%